Arterial Hypertension and Diabetes Mellitus: Therapy with Telmisartan, Interrelation Modeling, Approaches to Diagnosis and Complex Therapy - Evgeniya Malashenko (Journal of Global Pharma Technology, 2016)
Diabetes mellitus (DM) is an illness for an increasing number of people. Among the consequences that DM leads in the first place can be called degradation changes in the body, ultimately leading to limited physical capabilities. In DM, one of the related phenomena is a high risk of cardiovascular diseases (CVDs). This is due to the following factors: a) already the presence of risk factors before the DM development; b) the presence of obesity; c) arterial hypertension (AH). AH is present in 75-80% of patients with DM type 2, with half of them die. Due to the fact that AH and DM have a pathogenetic relationship, this fact naturally increases the risk of death. On the basis of data from Polyclinic No. 3 in St. Petersburg (Russia), a group of 200 patients with DM (female, age range 45-65) with concomitant AH were selected. The control group consisted of 100 females of the same age. Therapy was carried out with Telmisartan, with a dosage of 85 mg for a period of 8 weeks. As a result of the therapy, telmisartan has shown a positive effect on such parameters as carbohydrate metabolism and insulin resistance, as well as lipid metabolism. For patients with metabolic syndrome, during the period of therapy, telmisartan was noted to significantly (p≤0.05) reduce the rates associated with lipid metabolism. First of all it affected the cholesterine rate in the blood .Also obtained reliable data on the triglycerides reduction (TG), from 1.67 mmol/l 2.0 times more than half of the patients (41% of 75% who had elevated TG levels) undergoing telmisartan therapy. In addition, a decrease in the load on the AH time index, as well as a decrease in microalbuminuria rate was noted in patients. This indicates the organ-protective effect of telmisartan therapy. Permanent control of blood pressure is of primary importance for CVD prevention in patients with DM. When prescribing an antihypertensive agent, it is necessary to take into account RAAS-blocking drugs (renin-angiotensin-aldosterone system). Telmisartan has shown a positive effect on carbohydrate metabolism, reduced the elevated lipids levels (in particular, TG), and also affected insulin resistance.Keywords: DM (diabetes mellitus), AH (arterial hypertension), CVD (cardiovascular disease), telmisartan.